Perceived stress and adherence to prevention measures during pandemic covid-19 phase among midwives in hospital Universiti Sains Malaysia - Rosle, Nur Shafiqah Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Perceived stress among midwives influences the adherence to prevention measures, especially during a pandemic. Midwives’ mental health status is also associated with perceived stress. A cross-sectional study was conducted on 63 midwives in Hospital USM. A self-administered questionnaire was distributed to midwives that fit the inclusion criteria. The general objective of this study is to determine the level of adherence to prevention measures and level of perceived stress during pandemic COVID- 19 among midwives in Hospital USM. Besides, to determine the association between level of adherence to prevention measures with level of perceived stress during pandemic COVID-19 phase and association between socio-demographic characteristics (level of education, year of work experiences, and having children) with level of perceived stress during pandemic COVID-19 phase. The data were analysed by descriptive statistics and Pearson Chi-Square test, using Statistical Package for Social Sciences (SPSS) version 26.0. The findings showed that midwives in Hospital USM have moderate level of perceived stress (n=52, 82.5%). In addition, they also have good level of adherence to prevention measures (n=52, 82.5%). In term of the association, there was a significant association between level of adherence to prevention measures with level of perceived stress during pandemic COVID-19 phase (p-value <0.05), while there was no significant association between socio-demographic characteristics (level of education, year of work experiences, and having children) with level of perceived stress during pandemic COVID-19 phase (p-value >0.05). Thus, suitable action such as awareness and educational program must be done to help reduce the stress level with maintaining good compliance to prevention measures.